Information Sharing, Holdup, and External Finance: Evidence from Private Firms - Bird, Andrew; Karolyi, Stephen A; Ruchti, Thomas G (Review of Financial Studies, 2019)
Abstract To mitigate holdup by an informed incumbent lender, a private borrower may publicly share information in order to increase lender competition. Despite proprietary costs, a subset of private borrowers voluntarily share private information in loan and credit underwriting agreements. These borrowers switch lenders at a 16% higher rate and receive lower loan financing costs. For private firms that go public, we analyze changes in the net benefits of information sharing and study the potential estimation bias from unobservable borrower quality. This setting corroborates our inference that voluntary information sharing reduces lender holdup and alleviates financial constraints for private firms. Received May 25, 2017; editorial decision August 8, 2018 by Editor David Denis.